Set Kesempatan Investasi : Konstruksi dan Analisis Hubungannya dengan Kebijakan Pendanaan dan Dividen - fitrijanti, TetTet; Hartono, Jogiyanto (The Indonesian Journal of Accounting Research, 2002)
The primary objective of this research is examining correlation of three kinds of IOS proxies with realized growth after period of measuring the IOS level (t+l until t+5). The three kinds of IOS proxies are single empirical rasio (market to book value of asset or MVABVA , market to book value of equity or MVEBVE, price to earning per-price or PER, capital expenditure to book value of asset or CAPBVA and capital expenditure to market value of asset or CAPMVA), instrumental variable (VIIOS) and factor score (Skor). The results of one tailed Spearman Rank Correlation analysis show that all of IOS proxies positively correlated with realized growth of sales t+l, book value of equity t+l and book value of asset t+1. The common indeks of IOS, VIIOS and Skor, in the average have higher correlation coeffisients than single ratio IOS level of a company has to be evaluated every one year, because realized growth t+2 and so on have not been able to be predicted yet exactly using all of alternates IOS proxies.All of alternates IOS proxies from the primary hypothesis are used to examine the explanatory power of IOS in financing and dividend policy model. The results show that the growth firms have lower financing (measured by ln market debt to equity) and dividend (measured by ln dividend yields) policy than non growth firms. Contracting cost hypothesis explains the empirical relationship between IOS level, financing and dividend policy.The size of growth companies measured by lg asset higher than non growth companies. Contracting cost and secured debt hypothesis explain that, large companies have higher debt financing policy (measured by ln market debt to equity) than little companies. My opinion is there is conversely explanation between contracting cost hypothesis about association between IOS and debt financing policy, contracting cost and secured debt hypothesis about association between size of companies and debt financing policy and the consistent phenomenon that the growth companies are the large companies. But the result about dividend policy is consistent with contracting cost and pecking order hypothesis that the growth (large) companies have lower dividend policy (measured by ln dividend yields) than non growth (little) companies.